1970
DOI: 10.1002/jlac.19707390108
|View full text |Cite
|
Sign up to set email alerts
|

Zur Photolyse von 1‐Acyl‐benzotriazolen

Abstract: Die Photolyse von 1-Acyl-benzotriazolen wird in Abhangigkeit von Solvens, Konzentration und eingestrahlter Wellenlange untersucht. Im photochemischen Primarschritt spaltet sich Stickstoff ab; die Diradikale stabilisieren sich durch Wasserstoff-Abstraktion, Addition von Losungsmittel-Molekulen, RingschluO-Reaktionen unter Wasserstoff-Verschiebung und Polymerisation. Die Konkurrenz dieser Prozesse llBt sich an Hand der Ausbeuten der gebildeten N-Acyl-aniline, 2-Acylamino-biphenyle und des Phenanthridons verfolge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
2

Year Published

1970
1970
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…It has previously been asserted that only benzoxazoles are formed on pyrolysis, phenanthridinones on photolysis, and both on electron-impact-induced fragmentation of 1-benzoylbenzotriazoles. , …”
Section: Triazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been asserted that only benzoxazoles are formed on pyrolysis, phenanthridinones on photolysis, and both on electron-impact-induced fragmentation of 1-benzoylbenzotriazoles. , …”
Section: Triazolesmentioning
confidence: 99%
“…It has previously been asserted that only benzoxazoles are formed on pyrolysis, phenanthridinones on photolysis, and both on electron-impact-induced fragmentation of 1-benzoylbenzotriazoles. 406,407 The group of Moyano has employed the technique of catalytic flash vacuum pyrolysis over mixed oxides in a one-pot synthesis of 7H-dibenzo[b,d]azepin-7-one from phenacyl benzotriazole (eq 103). 408,409 The reaction can be considered a homologous version of the Graebe−Ullmann carbazole synthesis.…”
Section: 23-triazolesmentioning
confidence: 99%
“…Compound 24 is a 1-substituted triazole and is apparently photostable, although it has been observed that only 2-substituted 1,2,3-triazoles are photostable and others easily eliminate nitrogen. [19][20][21][22][23] This is probably not the case with compound 18, since in a photochemical reaction of compound 16 with diethylamine only 17d was isolated and no 18 could be detected, which contrasts with the corresponding thermal transformation. 6-Azidoazolopyridazines with Secondary Aliphatic Amines…”
mentioning
confidence: 99%
“…thiadiazolcarbonsaure-(4)-athylester, (111) : 172(3,5), 145(1,5), 144(16), 127(10), 116(3,5), 102(3), 101(5), 100(6), 99(10), 98(1), 88(21), 85(14),8 4 ( 3 ) , 83(5), 73(7), 72(36), 71(70), 70(7), 69(12), 67(1 l), 60(2), 59(21), 58(5), 47(4), 46(6), 45(56), 44(1 I), 43(15), 4 1 ( 9 ) , 40(4), 39(25), 3 8 ( 8 ) , 3 7 ( 4 ) , 3 0 ( 3 ) , 29(100). 4-Acetyl-5-methyl-1,2,3-thiadiazol, (IV) : 142(1), 115(3), 114(30), 99(3), 76(4), 73(4), 72(33), 71(26), 70(3), 69(7), 67(14), 59(7), 45(16), 44(1,5), 43(100), 39(15), 38(5), 3 7 ( 4 ) .…”
unclassified